2019
DOI: 10.1558/jld.39952
|View full text |Cite
|
Sign up to set email alerts
|

Language discrimination in Germany

Abstract: Language attitudes matter; they influence people's behaviour and decisions. Therefore, it is crucial to learn more about patterns in the way that languages are evaluated. One means of doing so is using a quantitative approach with data representative of a whole population, so that results mirror dispositions at a societal level. This kind of approach is adopted here, with a focus on the situation in Germany. The article consists of two parts. First, I will present some results of a new representative survey on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Accordingly, the standard language ideology of Standard German and its high levels of prescriptivism are wellevidenced in research, e.g. (Adler, 2019;Maitz & Elspaß, 2011). Unlike Standard Luxembourgish, Standard German is the medium of instruction and also a subject in the schools of our Belgian speech community.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, the standard language ideology of Standard German and its high levels of prescriptivism are wellevidenced in research, e.g. (Adler, 2019;Maitz & Elspaß, 2011). Unlike Standard Luxembourgish, Standard German is the medium of instruction and also a subject in the schools of our Belgian speech community.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, attitudes towards native speakers of Standard German are shown to be overwhelming positive in contrast to its vernaculars and other standardized majority languages, e.g. (Adler, 2019;Schoel et al, 2012). Accordingly, the standard language ideology of Standard German and its high levels of prescriptivism are wellevidenced in research, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is even mandatory for politicians to speak the local dialect in Bavaria. In particular, the Bavarian dialect of Germany holds a significant and independent position within the conceptual framework of languages ( Adler, 2019 ). A survey revealed that the Bavarian dialect is considered the second most appealing German dialect (29,6%), after the Northern German dialect (34,9%), while only about 7% found the Berlin dialect attractive ( Gärtig et al, 2010 ; Adler and Plewnia, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, attitudes towards Standard German are shown to be overwhelmingly positive when compared to other standardised languages present in Germany, such as English, Turkish and French (Rothe 2012;Schoel et al 2012a). Similarly, studies show more positive attitudes towards Standard German in contrast to its vernaculars in Germany and outside, e.g., in autochthon minority communities (Adler 2019;Deminger 2000;Schoel and Stahlberg 2012). Finally, the prestige of Standard German is intertwined with high levels of prescriptivism and linguistic discrimination against vernaculars and regional variation (Davies 2006;Maitz and Elspaß 2012;Schmidlin 2011).…”
Section: Belgische Eifel/"deutschsprachige Gemeinschaft" In Belgiummentioning
confidence: 97%